Teaching strategies for text comprehension of basic education students - Alvarado Guevara, Erman (2020)
The study aimed at establishing the incidence of teaching strategies on the reading comprehension of basic education students. Hence, an applied methodology of quasi-experimental design was developed, with the application of the Solomon model of four intact groups. Innovative teaching strategies were tested and their results were gathered in instruments such as assessment tests that were validated by communication experts, and were also analyzed through descriptive and inferential statistics (Kruskal-Wallis), which proved that the use of these strategies improved significantly the expected learning outcome in text comprehension.